University Builder : Edgar Odell Lovett and the Founding of the Rice Institute - Boles, John B. (Book collections on Project MUSE., 2007)
Rice University, one of America's preeminent institutions of higher education, grew out of the vision, direction, and leadership of one man: Edgar Odell Lovett (1871?1957). University Builder is the fascinating story of this extraordinary educator and the unique school he created. Widely acknowledged, almost from its founding in 1912, as one of America's best universities, Rice is distinguished as both the smallest and the youngest institution in the top tier of American universities. In telling the tale of Lovett and his innovative, enduring vision for Rice, John Boles provides both a compell.